The energy landscape predicts flight height and wind turbine collision hazard in three species of large soaring raptor - Emily Shepard (Journal of Applied Ecology, 2017)
Flight height was examined in a range of soaring raptors in order to predict the potential collision risk between these birds and wind turbines. This study developed a new method to account for the uncertainty in measurement of flight height from GPS-based measurements of altitude. The results indicate that species vary in their collision risk in line with expectations based on body size. In addition, collision risk can be predicted from thermal uplift potential. The new methods can be applied to other systems to examine collision risk.